Level of and Related Factors to Diabetes Awareness among Diabetic Adults by Gender: Based on Data from the Korean National Health and Nutrition Examination Survey - Ihn Sook Jeong; Chan Mi Kang (Elsevier, 2021)
Purpose: This study aimed to determine the level of awareness about diabetes mellitus (DM) and identify the associated factors among diabetic adults in Korea by sex, using data from most recent nationwide representative survey. Methods: Secondary data analysis was conducted using data obtained from the Korean National Health and Nutrition Examination Survey VII (2016-2018). In total, 2,026 participants (1,049 men, 977 women) aged ≥30 years with DM were included. Data were analyzed using a complex sample analysis considering the combined sampling weight for 3 years. Odds ratios and 95% confidence intervals were calculated using stepwise multiple logistic regression analysis to identify the association between DM awareness (DA) and sociodemographic and health-related factors. Results: Researchers observed that 60.2% of men and 68.4% of women had DA. DA levels in both men and women were higher in those who were older, less educated, had normal weight, had hypertension and/or dyslipidemia, and had a family history of DM than in their counterparts. Having undergone a health screening in the past 2 years was associated with DA levels in men, whereas glycated hemoglobin levels of 5.7-6.4% were associated with higher DA levels in women. Conclusion: The level of DA is unsatisfactory. Although the DA level is slightly higher in women than in men, it needs to be improved regardless of gender. Most of the factors associated with DA levels are similar in both men and women. Nurses in the community setting should provide health education, conduct campaigns, and promote referral to medical services by targeting the high-risk groups with lower DA identified in this study.